The Role of AI in Shaping Reproductive Health Policies: Implications for Women’s Rights - Sharma, Sunita (Journal of Neonatal Surgery, 2025)
Artificial Intelligence (AI) is increasingly transforming the landscape of reproductive health policy, raising complex legal and ethical questions with profound implications for women's rights. This paper investigates the growing integration of AI technologies such as predictive algorithms in fertility tracking apps, virtual health assistants, and automated decision-making tools in clinical settings, and their impact on women's reproductive autonomy, privacy, and access to healthcare services. While these technologies promise improved efficiency, personalized care, and expanded access, they also present significant risks concerning data privacy, algorithmic bias, and unequal access. The opaque nature of AI systems often obscures how decisions are made, potentially reinforcing existing disparities in healthcare or undermining informed consent. Moreover, the commoditization of intimate health data through digital platforms raises critical concerns about surveillance and the exploitation of women’s bodily information by private entities. The paper further explores the inadequacy of existing legal frameworks to effectively regulate AI in this domain, especially in safeguarding bodily integrity and reproductive justice. The study identifies best practices and gaps in current approaches to AI governance in reproductive health by drawing on international examples from jurisdictions such as the European Union and the United States. It emphasizes the need for rights-based reforms that prioritize transparency, accountability, and inclusivity in the design and deployment of AI tools. The analysis also calls for interdisciplinary collaboration among technologists, legal scholars, healthcare professionals, and feminist advocates to ensure that AI technologies advance rather than hinder reproductive justice. By situating AI within broader socio-legal and gendered contexts, the paper argues for a governance model that foregrounds women's rights, equity, and dignity in all aspects of reproductive health technology. This study contributes to the growing discourse on ethical AI by advocating for a future where innovation does not come at the expense of human rights, particularly those of women navigating reproductive choices.